2021 IEEE 18th International Conference on Mobile Ad Hoc and Smart Systems (MASS) 2021
DOI: 10.1109/mass52906.2021.00054
|View full text |Cite
|
Sign up to set email alerts
|

np-CECADA: Enhancing Ubiquitous Connectivity of LoRa Networks

Abstract: Long Range Wide Area Networks (LoRaWAN) offer ubiquitous communications for The Internet of Things (IoT). However, there are many challenges in rolling out LoRaWAN -mainly scalability, energy efficiency, Packet Reception Ratio (PRR), and keeping the channel access as simple as unslotted ALOHA. To this end, we design non-persistent Capture Effect Channel Activity Detection Algorithm (𝑛𝑝-CECADA), which is a novel, distributed protocol for the MAC layer of LoRaWAN. It utilizes Channel Activity Detection (CAD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They leverage Semtech's CAD mechanism [12] without considering the cases where the CAD fails to detect an ongoing transmission. But Semtech's CAD has reliability issues [13,14,24]. Experiments showed that CAD gets unreliable at distances less than 400 m in dense urban environments.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…They leverage Semtech's CAD mechanism [12] without considering the cases where the CAD fails to detect an ongoing transmission. But Semtech's CAD has reliability issues [13,14,24]. Experiments showed that CAD gets unreliable at distances less than 400 m in dense urban environments.…”
Section: Related Workmentioning
confidence: 99%
“…does not discard its use in np-CECADA [13]. The authors considered CAD ranges measured in good line-of-sight condition therefore got an optimistic performance evaluation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations